Literature Review: Pengaruh Model Role Playing dengan Media Audio Visual terhadap Minat Belajar Siswa pada Pembelajaran IPAS - Aprianti, Elsy Listi; Febriyanto, Budi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of the role playing learning model combined with audio-visual media on students' learning interests. The role playing model provides opportunities for students to actively participate by acting out certain situations that are relevant to the learning material, while audio-visual media is used to strengthen students' understanding through visualization and interesting narratives. The combination of the two is designed to create an interactive and fun learning atmosphere, so that it can increase students' motivation to learn. The research method uses a literature study approach by analyzing 20 scientific articles published during the 2020–2024 period. The data was collected through platforms such as Google Scholar and ResearchGate using the keywords